Increasing nutrient stress reduces the efficiency of energy transfer through planktonic size spectra. Issue 2 (30th September 2020) - Atkinson, Angus; Lilley, Martin K.S.; Hirst, Andrew G.; McEvoy, Andrea J.; Tarran, Glen A.; Widdicombe, Claire; Fileman, Elaine S.; Woodward, E. Malcolm S.; Schmidt, Katrin; Smyth, Tim J.; Somerfield, Paul J.
Abstract: Size‐spectral approaches quantify the efficiency of energy transfer through food webs, but theory and field studies disagree over how changes in temperature, nutrients, and extreme weather impact on this efficiency. We address this at two scales: via 6 years of weekly sampling of the plankton size spectrum at the Plymouth L4 shelf sea site, and via a new, global‐scale, meta‐analysis of aquatic size spectra. The time series showed that with summertime nutrient starvation, the energy transfer efficiency from picoplankton to macroplankton decreased (i.e., steepening slopes of the size spectra). This reflected increasing dominance by small cells and their microbial consumers. The extreme storms in winter 2013/2014 caused high metazoan mortality, steep size‐spectral slopes, and reduced plankton biomass. However, recovery was within months, demonstrating an inbuilt resilience of the system. Both L4 and our meta‐analysis showed steep slopes of normalized size spectra (median −1.11). This reflects much lower values, either of trophic transfer efficiency (3.5%) or predator–prey mass ratio (569), compared to commonly quoted values. Results from the meta‐analysis further showed that to represent energy transfer faithfully, size spectra are best constructed in units of carbon mass and not biovolume, and span a mass range of > 10 7 . When this range is covered, both the meta‐analysis and time series show a dome‐shaped relationship between spectral slopes and plankton biomass, with steepening slopes under increasingly oligotrophic and eutrophic conditions. This suggests that ocean warming could decrease the efficiency of energy transfer through pelagic food webs via indirect effects of increasing stratification and nutrient starvation.